Local Content-Based Learning Source for Senior High Schools with Augmented Reality : What are Students’ and Teachers’ Needs? - Asnawi, Asnawi; Wahyuni, Sri; Etfita, Fauzul; Mukhlis, Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aimed to analyze the needs of teachers and students in learning English with local content-based learning sources with augmented reality at the high school level in Riau Province. The research method was a survey with selected English teachers and students. Data collection was done by distributing questionnaires online with a google form. Quantitative data were analyzed using descriptive statistics. To confirm the validity of the quantitative data, an in-depth virtual interview was conducted with Google Meet. The results of the study showed that English teachers and students responded positively to developing these teaching materials with a mobile application. Specifically, from teachers’ perspective, developing local content-based learning sources with augmented reality could be possible in the narrative learning. Further, students believed that the development of this source could help the learning attainment. In conclusion, developing local content-based learning sources with augmented reality should be conducted.